Regulation of ZFP36 by lncOlfr29 promotes inflammation through NLRP3 - Cheng, Wenyue; Li, Fan; Zhang, Yuan; Gao, Yunhuan; Yang, Rongcun (Frontiers in Immunology, 2025)
ObjectiveThe functional state of macrophages is regulated by multiple factors and closely related to the occurrence and development of various diseases. The aim of this study is to discover a new regulatory factor in macrophages, which can serve as a target for disease prevention and treatment.MethodsLong non-coding RNA (lncRNA) lncOlfr29 was discovered through RNA sequencing. The functions of lncOlfr29 were investigated by bioinformatics analysis, lncOlfr29 shRNA silencing and overexpressing adenovirus, and lncOlfr29 knockout (KO) mice. To investigate the function of lncOlfr29 in vivo, we also established a Salmonella infection model and DSS-mediated colitis using lncOlfr29 KO mice.ResultsWe here identified a novel lncRNA named lncOlfr29 in macrophages and demonstrated that lncOlfr29 promoted inflammation by enhancing NLRP3-mediated IL-1 β maturation and pyroptosis of macrophages. In vivo experiments showed that lncOlfr29 could promote resistance to Salmonella infection and sensitivity to DSS mediated colitis. Mechanistically, lncOlfr29 could bind to zinc finger protein 36 (ZFP36) to eliminate the degradation of ZFP36 on NLRP3 mRNA. Knockout of lncOlfr29 led to a decrease of NLRP3 in cytoplasm, reducing macrophage pyroptosis and IL-1 β maturation.ConclusionOur data demonstrate that lncOlfr29 can regulate expression of NLRP3 through binding with ZFP36. These results will provide new insights into the treatment of inflammatory diseases.